(untitled) (KELAJAK SARI YANGI O’ZBEKISTON: ILM-FAN, TEXNOLOGIYA VA TA’LIM, 2026)
Communication etiquette, encompassing verbal and non-verbal elements, plays a pivotal role in fostering effective interactions in professional and academic environments. This article looks into the principles of verbal etiquette, such as active listening, polite language, and clear articulation, alongside non-verbal aspects including body language, facial expressions, and personal space. Drawing from established literature, the study examines how these components influence perceptions, build trust, and prevent misunderstandings in settings like conferences, meetings, and classrooms. Practical conclusions highlight the need for integrated training programs, while proposals include developing cross-cultural etiquette workshops and digital tools for self-assessment. Recommendations advocate for mindfulness in daily interactions to enhance professional relationships and academic success.